Orchids in the Montane forests of Peninsular Malaysia - Go, Rusea; Abdullah, Janna Ong; Nordin, Farah Alia; Md Isa, Siti Fatimah (Universiti Putra Malaysia Press, 2015)
Orchids in the Montane Forests of Peninsular Malaysia is a publication resulted from the many orchid exploration done by the authors team with collaboration mainly from Forest Department of Peninsular Malaysia since 1999. Inspired and invigorated by the immense array of colours, shapes, sizes, number of flowers and even fragrance those wild orchids possess, this book was written in a pictorial but scientifically inclined for the benefit of all groups of readers. Through the years of many botanical field study and explorations, a total of 490 species were recorded, which are represented by all five subfamilies of Orchidaceae. This book showcases only 267 orchid species out of the 490 recorded in montane forests, with their selection mainly based on the availability of the blooming plant photographs. The subfamily Cypripedioideae and Vanilloideae was represented with one genus, Apostasioideae by two genera, Orchidoideae by 15 genera, and Epidendroideae by 71 genera. The occurrence of the high number of species in the Montane region is attributed by the high moisture content (imbibed and stored by mosses and liverworts) and receive substantial amount of sunlight thus make it as a favourable ground for the orchids to thrive. We hope that this book will help to boost public awareness and cue yet another spat in support of efforts to ensure the longstanding existence of this exceptionally magnificent constituent of biodiversity. We have furnished current scientific name, brief gems description, global and local distribution, rarity, and endemism, for the benefit of all wild orchid enthusiasts and nature lovers. We hope you enjoy these magnificent Mother Nature’s gem, the wild orchids featured in this book.